AB0319 Comorbidities in ecuadorian patients with rheumatoid arthritis. (15th June 2017) - Maldonado, G; Rios, C; Ferro, C; Guerrero, R; Paredes, C; Moreno, M; Vallejo, C
Abstract : Background: Rheumatoid arthritis (RA) is associated with several comorbidities that reduce life expectancy. These comorbidities may be due to the rheumatic process itself, treatment or be independent, and include: anemia, osteoporosis, fractures, infections, gastric ulcers, myocardial infarction, depression, lymphoma and other malignancies. Objectives: The aim of this study is to determine the comorbidities in patients with an establish diagnosis of rheumatoid arthritis. Methods: A cross-sectional descriptive study was conducted in patients with an established diagnosis of RA according to the ACR 1987 criteria, from public and private rheumatology clinics in Guayaquil, Ecuador. The database included; demographics, comorbidities, habits, treatments, laboratory exams, number of swollen and tender joints, Visual Analog Scale (VAS), activity and disability index (DAS28 and HAQ-DI) and PHQ-9 for depression. The statistical program SPSS V. 22 was used to analyze the data and calculate frequencies, percentages, means, ranges, Spearman correlation and ANOVA coefficient. Statistical significance used was 0.05, with a 95% reliability. Results: 402 patients with a mean age of 50 years were included, 87.8% (353) women and 12.2% (49) men. 93.8% (377) were mestizos, 3.5% (14) White, 1.5% (6) Indigenous and 1.2% (5) Afro-Ecuadorians. As for the marital status 55.5% (223) were married, 15.4% (62) cohabiting, 12.4% (50) divorced, 8.5% (34) singles and 8.2% (33) widowers. 9.7% (39) of the patients smoked, 7.5% (30) ingested alcohol and 0.5% (2) drugs. The average age of onset of the disease was 41 years, with a median time from onset of symptoms and the first rheumatology visit of 28.7 months, median follow-up time of 51.8 months and average disease duration of 11 years. For comorbidities, 54.8% (147/268) had dyslipidemia, 28.4% (114) gastric disease, 23.6% (95) hypertension, 20.1% (81) obesity, 19.6% (79) depression, 15.2% (61) thyroid disease, 12.4% (50) of the sexual involvement, 10.7% (43) allergies, 10.4% (32/307) hypertransaminasemia, 9.3% (21/225) anemia, and 6.7% (27) diabetes mellitus. 32.3% (114) of women have had at least one abortion. The PHQ-9 medium was 5.3; according to this 11.2% (45) corresponded to mild depression, 4.5% (18) moderate depression, 3.2% (13) moderately severe depression and 0.7% (3) severe depression. As for the other indicators of disease activity, the average for the number of painful joints was 5 (0–28), swollen joints 4 (0–26), patient VAS 3.9 (0–10) and doctor VAS 3.4 (0–10). In laboratory data, 67.4% (215/319) had positive ESR, 64.8% (149/230) PCR, 90.5% (182/201) anti CCP positive, and 94.4% (286/303) RF. Conclusions: This is the first study of comorbidities in patients with RA in Ecuador. Patients with RA have a high prevalence of comorbidities and risk factors, which is why physicians should be prepared to prevent them and offer an early treatment. Disclosure of Interest: None declared